2019
DOI: 10.1172/jci.insight.128248
|View full text |Cite
|
Sign up to set email alerts
|

Platelet bioenergetics correlate with muscle energetics and are altered in older adults

Abstract: P-MRS were also performed in older adults. RESULTS. Maximal and ATP-linked respiratory rate measured in platelets from older adults correlated significantly with muscle maximal respiration (r = 0.595; P = 0.003) and maximal ATP production (r = 0.643; P = 0.004; by 31 P-MRS) in the same individuals. Comparison of platelet bioenergetics in older and younger adults showed lower basal and ATP-linked respiration in older adults. Platelets from older adults also showed enhanced proton leak, which was due to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…Blood cells contain fully functional mitochondria, and are abundant, self-renewing, and minimally invasive to obtain. Our group and others have successfully employed Seahorse XF and/or Oroboros to circulating cells to demonstrate that this methodology is feasible [ 43 , 44 ], reproducible in human populations [ 40 ], and that bioenergetics of circulating cells reflect bioenergetics in solid tissues such as the heart [ 42 ], skeletal muscle [ 42 , 45 ], brain [ 46 ], and lungs [ 47 ]. Further, these studies demonstrate alterations in blood cell bioenergetics in a number of natural biological conditions (e.g aging) or pathologies, and correlate with physical or clinical parameters of these conditions [ 45 , [47] , [48] , [49] ].…”
Section: Measurement Of Mitochondrial Bioenergetics In Human Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Blood cells contain fully functional mitochondria, and are abundant, self-renewing, and minimally invasive to obtain. Our group and others have successfully employed Seahorse XF and/or Oroboros to circulating cells to demonstrate that this methodology is feasible [ 43 , 44 ], reproducible in human populations [ 40 ], and that bioenergetics of circulating cells reflect bioenergetics in solid tissues such as the heart [ 42 ], skeletal muscle [ 42 , 45 ], brain [ 46 ], and lungs [ 47 ]. Further, these studies demonstrate alterations in blood cell bioenergetics in a number of natural biological conditions (e.g aging) or pathologies, and correlate with physical or clinical parameters of these conditions [ 45 , [47] , [48] , [49] ].…”
Section: Measurement Of Mitochondrial Bioenergetics In Human Diseasementioning
confidence: 99%
“…Our group and others have successfully employed Seahorse XF and/or Oroboros to circulating cells to demonstrate that this methodology is feasible [ 43 , 44 ], reproducible in human populations [ 40 ], and that bioenergetics of circulating cells reflect bioenergetics in solid tissues such as the heart [ 42 ], skeletal muscle [ 42 , 45 ], brain [ 46 ], and lungs [ 47 ]. Further, these studies demonstrate alterations in blood cell bioenergetics in a number of natural biological conditions (e.g aging) or pathologies, and correlate with physical or clinical parameters of these conditions [ 45 , [47] , [48] , [49] ]. Altered platelet bioenergetics have been measured in neurologic [ 46 ], metabolic [ 46 ], hematologic [ 44 ], cardiopulmonary [ 47 , 49 , 50 ], and infectious diseases [ 51 ] ( Fig.…”
Section: Measurement Of Mitochondrial Bioenergetics In Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…PLTs have been suggested to reflect the systemic effects of exercise on multi-organ systems based on existing data on the release of different cytokines, ions, metabolites and tricarboxylic acid (TCA) cycle intermediates from contracting muscles to the blood stream (primarily span-2 metabolites: succinate, malate, and fumarate), which are further affecting succinate receptor 1 (SUCNR1) positive cells such as PLTs in a dose-dependent manner (Gibala et al, 1998;Lewis et al, 2010;Högberg et al, 2011;Ariza et al, 2012;Knechtle and Nikolaidis, 2018). Moreover, recent studies have demonstrated parallels between oxidative respiration of skeletal muscle mitochondria and those of PLTs (Tyrrell et al, 2016;Braganza et al, 2019;Rose et al, 2019). Thus, the well accepted association between cardiorespiratory fitness and OXPHOS capacity of skeletal muscles (Walsh et al, 2001;Daussin et al, 2008;Pesta et al, 2011;Jacobs and Lundby, 2013;Christensen et al, 2016) might also apply (at least partly) to PLT mitochondrial function (Tyrrell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, peripheral blood platelets have been increasingly used as a source of viable mitochondria to investigate cellular respiratory dysfunction in order to complement studies reporting organ-related mitochondrial dysfunction in various pathologies [ 14 ]. Due to the low invasiveness through which they are obtained (especially as compared to muscle cells), platelets are an attractive source of human mitochondria for studies of toxic effects elicited by statin exposure [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%